Niveles de estrés y estrategias de afrontamiento en Estudiantes de los últimos ciclos de la Facultad de Medicina Humana de la UNSM-T. 2015 - Valles Panduro, Betty Mayrene (2015)
A correlational quantitative cross-sectional study was conducted with prospective data collection in 38 students enrolled in the X, XI, XII, cycle the Faculty of Human Medicine, during the semester 2015-I, in order to determine the relationship between stress levels and coping strategies of the students referred to the last month of the semester and the last or last two years of his life. The technique used was the survey questionnaire by applying the Perceived Stress and Coping Questionnaire (COPE-28) The results were: More than 86% of students come from another city Department of San Martin and other Department, and the vast majority is dedicated only to the study (84.2%). 86.8% of students in the last cycles of the Faculty of Human Medicine live alone. The stress level of students of the Faculty of Human Medicine 1 or 2 years ago was back half (47.4%) with tendecia to low (28.9%); while in the last month the stress level was average (52.6%) but with a tendency to High level (26.3%). As stress levels, students of Human Medicine of the last three cycles, in the last or last 2 years of his life, had the highest level of stress in the dimensions "for self satisfaction" with 78.9%; The "Fear and Anxiety" with 52.6% and the dimension "tension, irritability and fatigue" dimension with a 42.1%. In the last month of his life, students of Human Medicine of the last three cycles, showed the highest stress levels in the dimension "Fear and Anxiety" with 42.1%; 50% a medium level of stress in the dimension "Self-regulation Satisfaction" and lower level of stress with 47.4% in the dimension "Overload". The level of coping strategy presented by the xi students during the semester 2015 - I was adjusted with 57.9%, with a tendency to Malo (26.3%). The level was coping according Regular size (55.3%) for the cultural dimension. Coping Well level only occurred in 31.6% for the psychological dimension. There is a significant relationship between levels of stress and coping makes 1 or 2 years ago, the level of coping Malo is related to high levels of stress (55.6%); whereas a month ago in lower stress level is directly related to a good level, coping (62.5%). In the last month of study during the semester 2015-I, students of the Faculty of Human Medicine, the dimension of stress: Social Acceptance Conflict presented a highly significant relationship with a value X2 = 21.393